Retraction: Synergistic action of star-shaped Au/Ag nanoparticles decorated on AgFeO2 for ultrasensitive SERS detection of a chemical warfare agent on real samples. Issue 9 (17th February 2022) - Barveen, Nazar Riswana; Wang, Tzyy-Jiann; Chang, Yu-Hsu
Abstract : Retraction of 'Synergistic action of star-shaped Au/Ag nanoparticles decorated on AgFeO2 for ultrasensitive SERS detection of a chemical warfare agent on real samples' by Nazar Riswana Barveen et al., Anal. Methods, 2020, 12, 1342–1352, DOI: ; 10.1039/C9AY02347J .